Autonomic conflict exacerbates long QT associated ventricular arrhythmias. (March 2018) - Winter, James; Tipton, Michael J.; Shattock, Michael J.
Abstract: This study tested the hypothesis that concomitant sympathetic and parasympathetic stimulation ("autonomic conflict") may act as a trigger for arrhythmias in long QT syndrome (LQTS). Studies were performed in isolated innervated rabbit hearts treated with clofilium (100 nmol/L); a potassium channel blocker. The influence of vagus nerve stimulation (VNS) on spontaneous ventricular arrhythmias was assessed in the absence/presence of sustained noradrenaline perfusion (100 nmol/L) and with sudden adrenergic stress (injections of noradrenaline into the perfusion line). Hearts were instrumented for a pseudo-electrocardiogram and monophasic action potential recordings. VNS, which slows heart rate, was associated with a stimulation frequency-dependent incidence of spontaneous early after-depolarisations (EADs) and ventricular tachycardia (VT), best predicted by the duration of the electrocardiographic T-wave and by triangulation of the ventricular action potential. In the presence of sustained (steady-state) noradrenaline perfusion, the incidence of EADs and VT with VNS was decreased from 73/55% to 45/27%, respectively. However, sudden adrenergic stress, imposed during periods of sustained VNS, was associated with a transient increase in the incidence of severity of observed arrhythmias, as indicated by an increase in the average arrhythmias score (1.6 ± 0.4 vs. 2.1 ± 0.7, p  = .01). Analysis of electrophysiological parameters suggests that sudden adrenergic stress is associated with a transient prolongation, and increased triangulation, of the ventricular action potential, which may predispose to triggered activity. This study demonstrates that autonomic conflict is a pro-arrhythmic stimulus in LQTS. However, combined adrenergic and parasympathetic stimulation has a complex relationship with arrhythmogenicity, with differences in the effects of steady-state adrenergic activation vs. sudden adrenergic stress. Highlights: Long QT syndrome associated arrhythmias were studied with dual autonomic stimulation. EADs and TdP were triggered by increased vagal tone. Sudden adrenergic stress increased the severity of observed arrhythmias. Arrhythmias were prevented by sustained adrenergic stimulation. The sequence of autonomic stimulation influences the severity of long QT arrhythmias.